Pengaruh Tinggi Sprinkler Meganet 24D Netafim Terhadap Kemampuan Irigasi dan Hasil Lengas Tanah - I Dewa Gede Jaya Negara; Lilik Hanifah; Humairo Saidah; Muh Syahid; Firdaus (Program Studi Teknik Sipil Fakultas Teknik Universitas Lancang Kuning, 2022)
Farming on narrow land is mostly done in urban areas with limited water sources, because irrigation canals are not accessible. In vacant land around housing, urban communities can usually still use it for farming, even with limited water sources, shallow wells. To support urban farming, it is necessary to support an efficient irrigation system such as small sprinkler irrigation on the market. This study aims to test the ability of the Meganet 24D Netafim small sprinkler on irrigation capability, both in depth and soil moisture (w) and uniformity (Cu) produced, on an area of ​​about 1 acre. The test was carried out on 4 variations of discharge (Q), sprinkler distance (Ls) and sprinkler height (hs). Data analysis was carried out on Q, w and large Cu. Based on the analysis results obtained Cu above 85% at 0.5 m and 0.75 m with Ls 3.5 m to 5 m and flow rate Q4 = 0.42l/sec to Q1 = 0.57/sec. At a duration of 20 minutes, the irrigation depth was 20 cm and w obtained about 9% - 13%.